2020
DOI: 10.1371/journal.pntd.0008449
|View full text |Cite
|
Sign up to set email alerts
|

Viability PCR shows that non-ocular surfaces could contribute to transmission of Chlamydia trachomatis infection in trachoma

Abstract: Background The presence of Chlamydia trachomatis (Ct) DNA at non-ocular sites suggests that these sites may represent plausible routes of Ct transmission in trachoma. However, qPCR cannot discriminate between DNA from viable and non-viable bacteria. Here we use a propodium monoazide based viability PCR to investigate how long Ct remains viable at non-ocular sites under laboratory-controlled conditions. Methods Cultured Ct stocks (strain A2497) were diluted to final concentrations of 1000, 100, 10 and 1 omcB co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Here, we illustrated the immense spectrum of infectious chlamydial burden and even broader spectrum of total chlamydial burden in untreated infection and how IFU : GCN reveals a heterogeneity of Ct growth with some samples predominated by replicating forms, and others by non-replicating forms, supporting our previous pilot study ( Lewis et al., 2014 ). However, our future studies would benefit from the use of a recently described Ct-specific viability-PCR capable of distinguishing viable from non-viable Ct ( Janssen et al., 2016 ; Janssen et al., 2018 ; Dukers-Muijrers et al., 2020 ; Janssen et al., 2020 ; Versteeg et al., 2020 ; Janssen et al., 2022 ; Vojtech et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we illustrated the immense spectrum of infectious chlamydial burden and even broader spectrum of total chlamydial burden in untreated infection and how IFU : GCN reveals a heterogeneity of Ct growth with some samples predominated by replicating forms, and others by non-replicating forms, supporting our previous pilot study ( Lewis et al., 2014 ). However, our future studies would benefit from the use of a recently described Ct-specific viability-PCR capable of distinguishing viable from non-viable Ct ( Janssen et al., 2016 ; Janssen et al., 2018 ; Dukers-Muijrers et al., 2020 ; Janssen et al., 2020 ; Versteeg et al., 2020 ; Janssen et al., 2022 ; Vojtech et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, clinical trials to assess novel strategies for intensified delivery of the SAFE strategy could be carried out. Research into the biology of trachoma in the region could be further investigated: routes of transmission of ocular C. trachomatis are only now being more fully explored, 2 , 4 while work on the relationship between the background conjunctival microbiome, pathogen genotype, host genotype and susceptibility to infection in different settings is in its infancy. 37–40 All of these factors could potentially contribute to persistence of disease after treatment and warrant further investigation in light of the large number of districts in Oromia where TF has not fallen below 5% after the recommended number of MDA rounds.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it could be the result of parents cleaning their children’s faces before examination, as they became aware that faces were being inspected from observing the examination of other children in the central location. This could potentially have a detrimental effect, facilitating transmission if faces are wiped with unclean fomites: the detection of viable C. trachomatis DNA on non-ocular sites has demonstrated that these surfaces can contribute to ongoing transmission, and has led to suggestions that washing of plastic, hands (skin) and cloths should be considered by trachoma programmes in addition to face washing [ 2 , 28 ].…”
Section: Discussionmentioning
confidence: 99%